ANALISIS EFEKTIVITAS DAN DAMPAK PROGRAM BANTUAN BEDAH RUMAH TERHADAP KESEJAHTERAAN MASYARAKAT RTM DI KECAMATAN KARANGASEM - Tavnia, Savira; Dewi, Putu Martini (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
Home renovation assistance program is one of the government programs in efforts to overcome poverty and community welfare. The house renovation assistance program in Bali Province has been implemented from 2010 - 2019 through a self-management mechanism. The purpose of this study was to analyze the effectiveness of the implementation of the house renovation assistance program in Karangasem District. In addition this study aims to analyze the impact of the implementation of the house renovation program on the welfare of poor households (RTM) before and after the house renovation program in Karangasem District. Based on the results of the analysis shows that the effectiveness of the house renovation assistance program in Karangasem District has a positive and significant effect on community welfare. The house renovation assistance program has a good impact on the people who need it as well as those who are less able in terms of household and residential facilities   Keywords: House Renovation Program, Effectiveness, and Community Welfare